THE INFLUENCE OF VOLUNTARY GLOBAL REPORTING INITIATIVE (GRI) ON THE PERFORMANCE OF INDONESIA LISTED COMPANIES - Hurian Kamela; Ryan Saputra Alam (UNIB Press, 2021)
The background of this research is Indonesian companies are still voluntarily using GRI compare to other countries' cases. The main thing is that the limited number of companies that use GRI can affect its performance. The organization's performance describes the company's financial ratios as one of the effective financial performance descriptions. This is related to economic factors that are internal to the company, such as GRI, CSR, and ESG. The purpose of this study was discussed because of the limited number of listed companies in Indonesia (listed in IDX) using the GRI G4 method globally, which is one of the highlights of this research. The data used for 4 years, namely 2016-2019 in Indonesia. This research methodology uses panel data regression. This study uses secondary data, namely from the company's financial statements and database streams (Thomson Reuters Eikon). The results of the study prove that GRI affects financial ratios. The same result also occurs in other variables, namely ESG affects financial ratios (ROA). The controversy is that companies that have been listed must pay more attention to developments in items in GRI to gain trust from foreign investors and confidence in the company's sustainability.